2015
DOI: 10.4103/0019-5049.165859
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthesia for patient with chronic obstructive pulmonary disease

Abstract: The chronic obstructive pulmonary disease has become a disease of public health importance. Among the various risk factors, smoking remains the main culprit. In addition to airway obstruction, the presence of intrinsic positive end expiratory pressure, respiratory muscle dysfunction contributes to the symptoms of the patient. Perioperative management of these patients includes identification of modifiable risk factors and their optimisation. Use of regional anaesthesia alone or in combination with general anae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…The greater susceptibility of COPD patients to the development of pneumonia may be due to their clinical characteristics, such as mucus production in patients with chronic bronchitis and the potential presence of pathogenic bacteria in the airways, which may increase during exacerbations and be associated with increased inflammation and the host immune response [20]. In addition, abdominal opening or inflation (in endoscopic surgeries) alter chest wall configuration and may cause mechanical dysfunction in COPD, predisposing to infection [21][22][23]. However, in our study it is striking that incidence of VAP was lower in both men and women with COPD compared to those without COPD, contradicting a number of earlier studies that identified COPD as an independent risk factor for development of VAP [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…The greater susceptibility of COPD patients to the development of pneumonia may be due to their clinical characteristics, such as mucus production in patients with chronic bronchitis and the potential presence of pathogenic bacteria in the airways, which may increase during exacerbations and be associated with increased inflammation and the host immune response [20]. In addition, abdominal opening or inflation (in endoscopic surgeries) alter chest wall configuration and may cause mechanical dysfunction in COPD, predisposing to infection [21][22][23]. However, in our study it is striking that incidence of VAP was lower in both men and women with COPD compared to those without COPD, contradicting a number of earlier studies that identified COPD as an independent risk factor for development of VAP [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…During EBLV procedures, ventilation is further compromised, as the respiratory passage is shared with bronchoscopy instruments, further limiting expiratory airflow. Ventilatory management should be targeted at reducing the dynamic hyperinflation, PEEPi, and air trapping [13]. Allowing a longer expiratory time (I/E ratio 1:3–1:4) is a major consideration to reducing air trapping and thereby decreasing the occurrence of ‘breath stacking’.…”
Section: Discussionmentioning
confidence: 99%
“…Lung ventilation is an important determinant for the transport of volatile agents to the alveolarcapillary interface and further affects the uptake of these agents into blood and the brain [13,14]. We speculated that the administration of salbutamol will accelerate the bulk transportation of sevoflurane, an inhalation anesthetic, to the alveoli through improved lung volume and uniform gas distribution to the lung, while simultaneously enabling the smooth elimination of sevoflurane from the lung and shortening the recovery time [2]. We also hypothesized that salbutamol would be helpful in controlling sputum expectoration and bronchial constriction via its bronchodilating effect on the airway, which eventually may decrease the occurrence of PPCs [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…It poses a special anesthetic challenge in patients with specific pathophysiologic pulmonary changes. In clinical practice, volatile anesthetics are commonly used for inducing and maintaining anesthesia owing to their bronchodilating properties [ 2 , 3 ]. However, the depth of anesthesia may not reach the desired level at a given time due to gas trapping or dynamic hyperinflation upon induction or during surgery, which may delay recovery after surgery [ 4 ].…”
Section: Introductionmentioning
confidence: 99%